Causes of Blindness and Visual Impairment in Nigeria: The Nigeria National Blindness and Visual Impairment Survey - Abdull, Mohammed M; Sivasubramaniam, Selvaraj; Murthy, Gudlavalleti V. S; Gilbert, Clare; Abubakar, Tafida; Ezelum, Christian; Rabiu, Mansur M; on behalf of Nigeria National Blindness and Visual Impairment Study Group (Investigative ophthalmology & visual science, 2009)
Determine causes of blindness and visual impairment among adults aged >or=40 years. Multistage, stratified, cluster random sampling with probability proportional to size procedures were used to identify a nationally representative sample of 15,027 persons >or=40 years of age. Distance vision was measured with a reduced logMAR tumbling E-chart. Clinical examination included a basic eye examination of all subjects and a more detailed examination of those who had presenting vision <6/12 in either eye. Cause for vision loss was assigned to all subjects with presenting vision <6/12 in any eye. Of the 15,122 persons aged >or=40 years who were enumerated, 13,599 (89.9%) were examined. In 84%, blindness was avoidable. Uncorrected refractive errors were responsible for 57.1% of moderate (<6/18-6/60) visual impairment. Cataract (43%) was the commonest cause of blindness (<3/60). Prevalence of cataract-related blindness was 1.8% (95% CI: 1.57-2.05) and glaucoma-related blindness was 0.7% (95% CI: 0.55-0.88). Increasing age was associated with increasing prevalence of all major blinding conditions. Females, illiterate persons, and residents in the North East geopolitical zone had significantly higher odds of cataract-induced blindness and severe visual impairment. The high proportion of avoidable blindness, with half being attributable to cataract alone and uncorrected refractive errors being responsible for 57% of moderate visual impairment, means that appropriate and accessible refraction and surgical services need to be provided. If priority attention is not given, the number of blind and severely visually impaired adults in Nigeria will increase by >40% over the next decade.